Matched and mixed cap derivatives in the tetracyclic indole class of HCV NS5A inhibitors. Issue 16 (15th August 2016) - Dwyer, Michael P.; Keertikar, Kerry M.; Chen, Lei; Tong, Ling; Selyutin, Oleg; Nair, Anilkumar G.; Yu, Wensheng; Zhou, Guowei; Lavey, Brian J.; Yang, De-Yi; Wong, Michael; Kim, Seong Heon; et al.
Graphical abstract: Abstract: A matched and mixed capping SAR study was conducted on the tetracyclic indole class of HCV NS5A inhibitors to examine the influence of modifications of this region on the overall HCV virologic resistance profiles.